The inter-connections of ∑ 3 boundaries in pure iron. (February 2017) - Wang, Weiguo; Chen, Song; Rohrer, Gregory S; Chen, Wenzhe
Abstract: An integrated method involving electron backscatter diffraction, five-parameter analysis and crystallographic analysis, was employed to determine the inter-connections of ∑ 3 boundaries in a cold rolled and annealed pure iron. Three types of inter-connections were observed, including {1 1 2}/{1 1 2}, {1 1 1}/{1 1 5} and {0 1 1}/{0 1 1} which are present in the samples annealed for 15, 30 and 45 min at 620 °C after cold rolling, respectively. The results indicate though {1 1 2}/{1 1 2} is considered as low energy inter-connection in pure iron, it is replaced by {0 1 1}/{0 1 1} during annealing. Graphical abstract: